Securing IoT communication: a module-LWE key exchange protocol with efficient error reconciliation technique - Alvary Kefas Kwala; Alpna Mishra; Anshu Kumar (Discover Internet of Things)
Abstract The widespread use of Internet of Things devices alongside advances in quantum computing presents urgent challenges for secure communication. RSA and ECC have become inadequate, prompting the need for Post-quantum Cryptography (PQC). This work introduces a novel reconciliation-based Module-LWE key exchange protocol that eliminates the traditional encapsulation-decapsulation structure in schemes like Kyber.KE, thereby reducing computational cycles, communication size, and memory footprint. Unlike Kyber and NewHope, the proposed design employs modular rounding with Peikert reconciliation, optimizing the entire key exchange process without requiring additional randomness or ciphertext transmission. By leveraging Peikert’s error reconciliation technique and modular rounding, the proposed protocol achieves a 15% reduction in computational cycles, a 78-byte reduction in communication size, and a 10% decrease in memory usage. Using Open Quantum Safe (OQS) benchmark data, we evaluate performance across Kyber512, Kyber768, and Kyber1024 levels, demonstrating the protocol’s superior energy efficiency and lightweight design. These improvements position our protocol as a secure, efficient, and scalable solution for post-quantum key exchange in resource-constrained environments such as embedded systems and IoT networks.